Use of colony-stimulating factor primary prophylaxis and incidence of febrile neutropenia from 2010 to 2016: a longitudinal assessment. (3rd June 2019) - Weycker, Derek; Bensink, Mark; Lonshteyn, Alexander; Doroff, Robin; Chandler, David
Abstract: Background: Guidelines recommend primary prophylactic use of colony-stimulating factor (PP-CSF) when risk of febrile neutropenia (FN) – based on chemotherapy and patient risk factors – is high. Whether and how PP-CSF use may have changed over time (e.g. due to guideline revisions, increasing use of myelosuppressive regimens, controversy regarding inappropriate CSF use), and whether there has been a concomitant change in the incidence of FN, is unknown. Methods: A retrospective cohort design and data from two US healthcare claims repositories were employed. The study population included patients who had non-metastatic cancer of the breast, colon/rectum, lung or ovaries, or non-Hodgkin's lymphoma (NHL), and who received myelosuppressive chemotherapy regimens with an intermediate/high risk for FN. For each patient, the first cycle of the first course was characterized in terms of PP-CSF use and FN episodes. Crude incidence proportions for PP-CSF and FN during the first cycle were estimated by calendar quarter (2010–2016); multivariable logistic regression models were used to estimate quarter-specific adjusted mean probabilities of FN by PP-CSF use. Results: The study population totaled 142, 730 patients with breast cancer (61%), colorectal cancer (14%), NHL (11%), ovarian cancer (10%) or lung cancer (5%). PP-CSF use increased from 52% in 1Q2010 to 58% in 4Q2016; pegfilgrastim was the most commonly used agent (>96% across quarters). PP-CSF administration on the same day as chemotherapy ranged from 8 to 11% until 1Q2015, and increased to 64% by 4Q2016. Adjusted incidence proportions for FN in the first chemotherapy cycle ranged from 2.7% (95% CI: 2.3–3.0) to 3.7% (95% CI: 3.1–4.3) among those who did not receive PP-CSF, and was 2.6% (95% CI: 2.5–2.7) across quarters among those who received PP-CSF. Conclusions: Although the use of PP-CSF is commonplace in current US clinical practice, underutilization in cancer patients receiving chemotherapy regimens with an intermediate/high risk for FN may still be an issue. Use of same-day PP-CSF increased markedly from the end of 2015, although this finding reflects (at least in part) increased uptake of pegfilgrastim delivered via an on-body injector as well as the recent change in clinical practice guidelines. Overall, patients receiving PP-CSF appear to have a lower risk of FN during the first cycle of chemotherapy.